Catholic Church Responses to Clergy-Child Sexual Abuse and Mandatory Reporting Exemptions in Victoria, Australia: A Discursive Critique - Graham, Hannah (International Journal for Crime, Justice and Social Democracy, 2015)
This article presents empirical findings from a critical discourse analysis of institutional responses by the Catholic Church to clergy-child sexual abuse in Victoria, Australia. A sample of 28 documents, comprising 1,394 pages, is analysed in the context of the 2012-2013 Victorian Inquiry into the Handling of Child Abuse by Religious and Other Organisations. Sykes and Matza's and Cohen's techniques of neutralisation and denial are used to reveal the Catholic Church's Janus-faced responses to clergy-child sexual abuse and mandatory reporting requirements. Paradoxical tensions are observed between Catholic Canonical law and clerical practices, and the extent of compliance with secular law and referral of allegations to authorities. Concerns centre on Church secrecy, clerical defences of the confessional in justification of inaction, and the Melbourne Response compensation scheme. Our research findings underscore the need for greater Church transparency and accountability; we advocate for mandatory reporting law reform and institutional reform, including adjustments to the confessional ritual